(untitled) (Research, Society and Development, 2021)
The association between inadequate intake of antioxidant micronutrients and lipid concentrations of adolescents participating in the Study of Cardiovascular Risks in Adolescents was investigated. Cross-sectional, multicenter, school-based study, carried out in 2013 and 2014, with 36,918 adolescents aged 12 to 17 years, from public and private schools, in Brazilian municipalities with more than 100 thousand in habitants. Participation frequencies (eligible) by macro-regions, sex, age and type of school were calculated. Food consumption data were obtained through a 24-hour Food Recall and the mean intake was analyzed. Biochemical evaluation was performed with CT, HDL-c, TG and LDL-c exams. Data were analyzed using Stata® software, version 15.1 and 95% confidence interval. Pearson’s chi-square test and multiple regression were used to estimate the Odds Ratio (OR) and measure the strength of association between the variables, with a significance of 5%. Inadequate vitamin E intake associated with elevated LDL-c in adolescents aged 12 to 14 years and hypertriglyceride average in boys aged 15 to 17 years in public schools. Vitamin B12 was related to low levels of HDL-c and elevated LDL-c in boys aged 12 to 14 years in public schools and with a lower chance of hypertriglyceride average in those aged 15 to 17 years. The inadequacy of manganese associated with low HDL-c and high LDL-c in girls aged 15 to 17. In conclusion, associations were found between inadequate consumption of vitamins E, B12 and Manganese and the lipid profile of the population studied.